Penyuluhan hukum Tentang Kedudukan Hukum Perangkat Desa Berdasarkan Undang-Undang Nomor 6 Tahun 2014 Tentang Desa - Ashari; Sarkawi; Johannes Johny Koynja (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
The existence of village officials is regulated in Law Number 6 of 2014 concerning Villages, Government Regulation Number 43 of 2014 in conjunction with Government Regulation Number 47 of 2015, and Regulation Minister of Home Affairs Number 83 of 2015 which has been amended by Ministerial Regulation Domestic Affairs Number 67 of 2017, Even though there is a clear legal basis, the practice in The field shows that the dismissal of village officials still often causes serious problem This is caused by non-compliance with regulations, the existence of vested interests politics, as well as the weak understanding of the village head and village officials themselves regarding the rules applicable law. Therefore, there is a need for legal counseling regarding the legal status of village apparatus in statutory regulations in order to provide understanding to the village head and village officials to minimize conflicts of interest in order to create better and more competitive village governance. The methods used in This counseling are carried out through lectures, discussions and questions and answers. This study concludes that the village head does not fully understand the regulations regarding dismissal and appointment of village officials by implementing this counseling, it is hoped that various practical problems such as inconsistencies in appointment and dismissal procedures village officials so that the potential for internal conflict can be minimized so that the process/dismissal becomes more transparent, objective and accountable.